A critical analysis of the auditing and reporting functions of Nigeria Extractive Industry Transparency Initiative (NEITI) Act 2007: Lessons for EITI countries. Issue 3 (19th August 2014) - Ihugba, Bethel Uzoma
Abstract : Purpose: This article examines the effectiveness of the legal response by Nigeria to the sustainable management and use of revenue from the extractive industry in its enactment of the Nigeria Extractive Industry Transparency Initiative (NEITI) Act 2007. It hopes to contribute to the development of Nigeria's and other countries' Extractive Industry Transparency Initiative (EITI) based regulations or policies intended for the sustainable exploitation and management of revenue from the extractive industry. Design/methodology/approach: The paper is qualitative and uses critical analysis to explore the potentials and limits of the NEITI Act vis-à-vis its promises and capabilities. The article concentrates on the analysis of the sections providing for the objectives of the Act, its functions, its auditing and reporting requirements and timeline for publications of audits and reports for purposes of transparency, accountability and public debate. Findings: The paper finds that although the intendment of the Act appears positive the sections providing for the achievement of its objectives and functions are bedevilled with several ambiguities, which undermine its effectiveness. Research limitations/implications: The NEITI Act is as yet neither a basis for the prosecution of any individual and/or organization nor been legally challenged in court. As such there is no case law to exemplify the practical application of its provisions. However, logical analysis and review of the Act suggests that more needs to be done to increase its effectiveness. Practical implications: The paper makes the case for the proper definition of terms, stipulation of clear timelines and creation of enforcement functions in legislations, especially in laws that aim to regulate potential irregularities that may provide huge financial rewards for perpetrators and/or undermine a society's socio-economic development. Originality/value: This paper boldly questions the effectiveness and functionality of the NEITI Act 2007 and lays out a framework for its improvement. Also due to serious dearth of scholarly work on NEITI Act 2007, this paper is the first research work to explore the effectiveness of the NEITI Act 2007 from a legal perspective.